Way to accomplish low carbon development transformation: A bibliometric analysis during 1995–2014. (February 2017) - Wang, Linyuan; Zhao, Lin; Mao, Guozhu; Zuo, Jian; Du, Huibin
Abstract: A bibliometric analysis of low carbon related publications is reported in this study in order to depict existing research activities and to identify future directions in this research field. These publications were retrieved from various databases such as: Science Citation Index (SCI), Social Science Citation Index (SSCI), Conference proceedings Citation Index-Science (CPCI-S) and Conference Proceedings Citation Index-Social Science & Humanities (CPCI-SSH). There is a notable growth associated with the body of knowledge on low carbon research. A total of 5445 records were obtained from these four major academic databases. Journal articles and proceedings papers are two frequently used document types representing 93.24% (5077 records) of the records and English is the dominant language with 5250 records (96.42%). The most productive subject is Energy & Fuels (1282 records) and the most productive journal is Energy Policy (313 records). China has largest number of publications related to low carbon. However, the USA accounts for the highest H-index (50). The Chinese Academic of Science is the organization with the most records (100 records) and the highest H-index (15). Four clusters are identified according to the analysis of co-occurrence keywords. Topics from Cluster (I) (central nodes as "climate change" and "renewable energy") are still vital to the low carbon research. However, their relative popularities declined over the past decade compared to other topics. This indicates more diverse topics from Cluster (II) (central nodes as "low carbon economy"), Clusters (III) (central nodes focusing on "low carbon", "energy" and "sustainability"), and Cluster (IV) (central node as "smart grid" interrelate with Cluster (I)) will be foci of future research endeavor in the coming decade. Highlights: Analyzed low carbon related literature during the last two decades. Revealed various publication characteristics via bibliometric analysis and h-index; Examined academic cooperation relationship via social network analysis. Identified the main research fields and analyzed their research status. Recommended future directions in the field of low carbon research.